The Relationship Between Children's Knowledge Level And Obesity Prevention Behavior Among Fourth, Fifth, And Sixth Grade Students At State Elementary School 74 In Bengkulu City In 2024 - Ayu, Anggra; Rohani, Tuti; Apriyanti, Delta (Universitas Dehasen Bengkulu, 2025)
Obesity in children aged 5-12 years in Indonesia is as much as 9.2% obesity. WHO data states that in 2022 more than 160 million children and adolescents are obese, from the data obtained also explains the prevalence of obesity in children and adolescents increased drastically from only 8% in 1990 to 20% in 2022. The purpose of this study was to determine the relationship between the level of children's knowledge and obesity prevention behavior in students of grades IV, V and VI of SD Negeri 74 Bengkulu City in 2024. The method used in this study is quantitative with a Cross sectional approach. The sampling technique is using Stratified random Sampling using a sample of 79 respondents representing grades IV, V and VI of SD Negeri 74 Bengkulu City. The results of the univariate test analysis showed that more than half of the respondents (54.4%) had sufficient knowledge, more than half of the respondents (54.4%) had poor prevention behavior. The results of the study using the chi-square test showed a relationship between knowledge and behavior (p = 0.008) in grades IV, V, and VI of SD Negeri 74, Bengkulu City. The researcher suggested that this study be used as a reference source for the relationship between children's knowledge levels and obesity prevention behavior in elementary school students.